2019
DOI: 10.1016/j.neuron.2019.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Leads to Cortical Under-Connectivity and Cognitive Impairment

Abstract: Highlights d Cortical connections decrease in a DiGeorge/22q11 deletion syndrome mouse model d Under-connectivity reflects reduced dendrite, axon, and synapse growth d Txrnd2, a 22q11 gene, regulates mitochondrial metabolism and neuron growth d Cortical connections and behavioral deficits are restored by anti-oxidant therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 71 publications
4
120
0
1
Order By: Relevance
“…It is noteworthy that the terms related to synaptic components were significantly enriched, such as GABA-ergic synapse, axon, cell adhesion, and cell morphogenesis, indicating that the dysfunction of synapses could be one key pathological basis of ASD, which is a commonly accepted viewpoint in the field [Gokoolparsadh et al, 2016]. In addition, genes involved in NADH dehydrogenase (ubiquinone) activity were enriched in overlapped DEGs, in agreement with the previous finding that mitochondrial dysfunction is involved in ASD and intellectual disorder [Goh, Dong, Zhang, DiMauro, & Peterson, 2014;Fernandez et al, 2019].…”
Section: Functional Annotation and Pathway Enrichment Of The Overlappsupporting
confidence: 88%
See 2 more Smart Citations
“…It is noteworthy that the terms related to synaptic components were significantly enriched, such as GABA-ergic synapse, axon, cell adhesion, and cell morphogenesis, indicating that the dysfunction of synapses could be one key pathological basis of ASD, which is a commonly accepted viewpoint in the field [Gokoolparsadh et al, 2016]. In addition, genes involved in NADH dehydrogenase (ubiquinone) activity were enriched in overlapped DEGs, in agreement with the previous finding that mitochondrial dysfunction is involved in ASD and intellectual disorder [Goh, Dong, Zhang, DiMauro, & Peterson, 2014;Fernandez et al, 2019].…”
Section: Functional Annotation and Pathway Enrichment Of The Overlappsupporting
confidence: 88%
“…The functions of module 1 and module 2 have been clearly linked to the pathomechanism of ASD [Gokoolparsadh et al, ]. For the module 3, mitochondrial dysfunction has recently been reported to cause cortical under‐connectivity and cognitive impairment in neurodevelopmental disorders [Fernandez et al, ]. In the Cortex‐Juvenile network (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrast between in vivo and in vitro data suggests that the effects of the 22q11.2 deletion on barrier function are not solely due to claudin-5 gene dosage, but more likely due to an interaction of genes in the deleted region or an exaggerated stress response in vitro. Of note are the 6 mitochondrial genes in the 22q11.2 deleted region (Maynard et al, 2008;Napoli et al, 2015), which may further contribute to compromise the BBB given the impaired mitochondrial function reported in other CNS cell populations in 22qDS (Fernandez et al, 2019;Li, Ryan, et al, in press). Furthermore, we have found that ICAM-1 is upregulated in the BBB, implicating differences in inflammatory/stress responses in 22qDS (Alvarez, Cayrol, et al, 2011;Daneman & Prat, 2014;Dietrich, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has also been recently demonstrated to lead to significant reductions in long range axonal connectivity. 55 Because structural connectivity is a required substrate for functional connectivity, OXT-induced changes in factors affecting anatomical connections between neurons could affect functional brain network organization (i.e., segregation and integration). Our general finding of impaired cortical functional connectivity in male offspring treated with OXT is broadly supportive of this notion.…”
Section: Discussionmentioning
confidence: 99%